2018
DOI: 10.3389/fmicb.2018.02129
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Cycling by a Low-Diversity Microbial Community in Deep Groundwater

Abstract: Olkiluoto, an island on the south-west coast of Finland, will host a deep geological repository for the storage of spent nuclear fuel. Microbially induced corrosion from the generation of sulphide is therefore a concern as it could potentially compromise the longevity of the copper waste canisters. Groundwater at Olkiluoto is geochemically stratified with depth and elevated concentrations of sulphide are observed when sulphate-rich and methane-rich groundwaters mix. Particularly high sulphide is observed in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 78 publications
(102 reference statements)
2
29
0
Order By: Relevance
“…The relative abundances of bacterial and archaeal 16S rRNA gene sequences in the springs were similar to the abundances found in other aquifer studies, and some similar taxa have also been reported previously (41)(42)(43)(44). Proteobacteria and Cyanobacteria composed a large portion of the 16S rRNA gene sequences from all of the Florida springs investigated here.…”
Section: Figsupporting
confidence: 89%
“…The relative abundances of bacterial and archaeal 16S rRNA gene sequences in the springs were similar to the abundances found in other aquifer studies, and some similar taxa have also been reported previously (41)(42)(43)(44). Proteobacteria and Cyanobacteria composed a large portion of the 16S rRNA gene sequences from all of the Florida springs investigated here.…”
Section: Figsupporting
confidence: 89%
“…The concentration of acetate in the Olkiluoto fracture fluids is often below the detection limit [40], as it was also in both studied fracture fluids (Table 1). However, it seems that detectable and even relatively high amounts of acetate can be found sporadically in the Olkiluoto fracture water [41] Nevertheless, acetate production is likely in these subsurface fluids, as both autotrophic and heterotrophic acetogens have been cultivated from many Olkiluoto fracture fluids [42], and an active pathway for acetogenesis has been detected in the studied OL-KR6/125-130 m fracture fluid by metagenomic and metatranscriptomic sequencing [18]. In addition to utilising acetate, some of the SRB also produce acetate as a by-product of sulphate reduction when organic compounds are incompletely degraded to acetate, such as Desulfovibrionaceae and Desulfovibrio species [43].…”
Section: Discussionmentioning
confidence: 98%
“…The genome of strain F-1 T possessed all genes for glycolysis via the Embden-Meierhoff-Parnas pathway. Surprisingly, the reductive pentose phosphate pathway in the genome of strain F-1 T is absent, although ribulose biphosphate carboxylase, key enzyme of rPP, was present in the proteomes of several Pseudodesulfovibrio strains (Bell et al 2018). Strain F-1 T is capable of utilizing molecular hydrogen as an energy source.…”
Section: Genome Analysismentioning
confidence: 99%